Narrativas de formadoras de professores de inglês - Angelo Augusto Peixoto Coutinho (2020)
The present research investigated how three professors from public universities build their identities as teacher educators and as English speakers. This study aimed at understanding how the paths taken by teacher educators may influence their current practices. Specifically, through this research, professional testimonials were generated regarding the teacher educator’s education and their relationship with the language they teach. In addition, the participants also had the opportunity to comment on their victories and defeats throughout their careers and how the fact that they are non-native English speakers affects their self-image and the expectations of both themselves and their students. The qualitative methodology involved narrative research through semi-structured interviews that originated the analyzed narratives. The results point to the fact that there are multiple sources that construct the participants' identities, and these sources relate to their experiences in language institutes, influence of former teachers and their relationship with English. First, the analysis indicates that participants seem to have been interested in language teaching because of the influence of former teachers and by observing their practice. The second point which could be observed is that, in the participants' view, teacher educators change and transform their students in a context of intense interaction with them, but given the curricular and institutional difficulties and fragmentations, many professors do not see themselves as teacher educators. The third data analyzed leads us to believe that participants possibly associate their school experiences to a somewhat frustrating thing and that students' resistance to the concepts taught makes the classroom more challenging. However, the change and transformation observed in students may be seen as a great victory for them. When it comes to the relationship of the participants and their students with English, it has been observed that probably, for them, not being native speakers do not cause them any insecurity. Actually, any English teacher should, in their opinion, demystify this view of the native speaker as the ideal speaker. In the case of students, however, the participants still observe deculturation, the overvaluation of the cultures of English-speaking countries and a certain insecurity. Finally, with regard to the future of English teaching in Brazil, participants who are optimistic tend to see, in the future, a greater presence of critical and decolonial approaches in the classroom which seems to give them hope even if the changes are small. On the negative side of language teaching in Brazil, we see the possible surrender to foreign capital and the possible annulment of decolonial efforts.